Glia Maturation Factor Beta as a Novel Biomarker and Therapeutic Target for Hepatocellular Carcinoma - Sun, Wan; Hu, Changchang; Wang, Tianyu; Wang, Juan; Zhang, Jieping; Gao, Furong; Ou, Qingjian; Tian, Haibin; Jin, Caixia; Xu, Jingying; Zhang, Jingfa; Xu, Guo-Tong; et al. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the most common types of cancer. The novel sensitive biomarkers and therapeutic targets are urgently needed for the early diagnosis of HCC and improvement of clinical outcomes. Glia maturation factor-β (GMFB) is a growth and differentiation factor for both glia and neurons and has been found to be tightly involved in inflammation and neurodegeneration conditions. In our study, the expression level of GMFB was significantly up-regulated in patients with HCC and positively co-expression with tumor node metastases (TNM) stage and histopathological grade of HCC. The high expression level of GMFB was remarkably associated with poor overall survival, which mainly occurred in males rather than females. Multivariate analysis revealed GMFB to be an independent prognostic factor for overall survival in patients with HCC. Results of Gene Ontology (GO) and KEGG pathways analysis showed that down-regulation of pathways related to protein translation and mitochondria function were enriched. Protein-protein interaction analysis revealed the central role of mitochondria protein in HCC. The downregulation of genes involved in glycolysis and gluconeogenesis was observed among the co-expression genes of GMFB. Knockdown of GMFB in Hep3B significantly inhibited proliferation, migration, and invasion of Hep3B cells, and also downregulated the expression levels of some of metal matrix proteinase (MMP), increased mtDNA copy number and loss of mitochondrial transmembrane potential. GMFB influences the malignancy rate of HCC possibly through regulation of the expression of MMPs, mtDNA function and glycolysis. We proposed that GMFB was a promising HCC diagnostic and prognostic biomarker and therapeutic target in HCC.